A study of anti-SARS-CoV-2 antibody positivity in Duhok City, Iraq - Nawfal R Hussein; Guleer H Shahab; Narin A Rasheed; Alind N Ahmed; Reving S Salih; Ahmed S Mahdi; Sabeeha A Mansour; Shaveen Mahdi; Ibrahim A Naqid; Nawshan Ibrahim; Dildar H Musa; Zana SM Saleem (Journal of Infection in Developing Countries)
Introduction: The study aimed to investigate the positivity rate of anti-SARS-CoV-2 antibodies and associated factors.